SNX11 Deletion Inhibits Dabie bandavirus Infection by Interfering with the Assembly of V-ATPase - Tiezhu Liu; Xueqi Wang; Yang Fang; Ping Zhang; Qiang Sun; Jiandong Li; Shiwen Wang (Pathogens, 2025)
SNX11, a sorting nexin protein localized on the endosomal membrane, is an important protein closely related to protein sorting and endosomal trafficking. Previously, through a genome-wide CRISPR screening, we identified SNX11 as a critical protein for the entry of Dabie bandavirus. SNX11 deletion significantly inhibits the replication of Dabie bandavirus. We further discovered that the loss of SNX11 alters endosomal pH, potentially affecting the release process of Dabie bandavirus from endosomes to the cytoplasm. However, the mechanism by which SNX11 modulates endosomal pH and whether SNX11 deletion similarly inhibits other viruses remain to be elucidated. This study reveals that SNX11 can interact with the V1 subunit of the endosomal proton pump V-ATPase, affecting the expression level of this subunit on the endosomal membrane and thereby disrupting the assembly of V-ATPase. Additionally, we found that SNX11 deletion significantly inhibits the replication of dengue virus, hantavirus, and influenza virus. These findings suggest that SNX11 may be a key protein in the process of viral infection and could serve as a broad-spectrum antiviral target.